Comprehensive analysis of sugarcane (Saccharum spp) gene expression changes in response to drought and re-watering conditions - Silva, Danielle Izilda Rodrigues da (2017)
The exhaustion of oil fields together with the undesirable effects of its use has turned sugarcane into an attractive crop for the biofuel market, increasing its economic and environmental importance. The position of Brazil as the world\'s major sugarcane producer and the need to expand the planted area to soil with less favorable conditions makes the study of drought, one of the abiotic stresses affecting the most of this crop yield, essential for the future of Brazil as the main exporter of this commodity. This work has the aim of providing a comprehensive analysis of sugarcane drought responses in the physiological and molecular levels. In order to do that we followed four strategies. First, we performed the analysis of physiology and transcriptome (microarray) of drought stressed sugarcane plants in three time points (4 days of stress, 6 days of stress and re-watering) of a greenhouse experiment. The plant material analyzed was leaves and roots. Second, aiming to identify different genes and new patterns of expression it was done the analysis of RNA-Seq from the most discrepant condition, from both leaves and roots, found by the microarray, third, we performed the analysis of a drought progression experiment through physiology and qRT-PCR of selected candidate genes and forth we built co-expression networks to detect interesting patterns. Physiology analysis showed that plants were under moderate to severe water stress with decreases of up to 97% in photosynthesis. Microarray data indentified 7,867 unique SAS with a fold change of more than 2 or less that 0.5, and 575 unique SAS differentially expressed. The analysis of the identified sequences allowed the observation that in leaves after 4 days of stress, the plant is mostly transducing the signal from the environment, while after 6 days and after rehydration there is a more functional response of the plant, with re-watering leading the metabolism back to homeostase. In the case of roots, it was observed a similar response, however roots take longer to go back to the initial condition, since several genes are still being down-regulated even after re-watering. There are also pathways presenting an opposite pattern in the analyzed tissues, being activated in one tissue but repressed in the other, such as Phenylpropanoid Biosynthesis pathway. Furthermore, while in leaves there is a restriction on photosynthesis, on roots it seems to be a restriction on growth. RNA-Seq de novo assembly showed 28,240 differentially expressed features in leaves and 7,435 in roots, while using the reference genome (unpublished data) it was possible to identify 38,317 differentially expressed genes in leaves and 7,649 in roots, and the analysis of KEGG pathways indicate that ABA has a major role in both leaves and roots responses to drought, but in leaves there is an interplay of phytohormones. Drought progression experiment confirms the results obtained from microarray and shows that when stress is extreme, gene expression starts to decrease, suggesting the plant might be entering in senescence. Co-expression analysis allowed the determination of three modules correlated with physiological parameters altered during water stress, and lead to the identification of some possible hub genes that may be important for sugarcane responses to drought. Furthermore, it was possible to identify genes that through both co-expression and qRT-PCR analysis had similar patterns of expression. Altogether, these results give us a comprehensive view of the alterations in sugarcane responses to water stress and helped us gain insight for defining better suited candidate genes for plant breeding.